Novel food processing innovations to improve food safety and health - McHugh, T. H.; Avena-Bustillos, R. J. (Progress in Nutrition, 2011)
SummaryInnovative food processing can be used to improve safety of specialty crops and their co-products, while improving sustainability of agricultural and food processing operations and enhancing overall nutritional quality of foods for both domestic and international consumers. The potential of various innovative food processes, many of which have been developed at the USDA, Agricultural Research Service, Western Regional Research Center in Albany, CA, and some of which have been transferred into commercialization through partnerships with industry will be discussed. Innovative technologies such as film casting, ultraviolet, infrared, and solar energy treatments, can enhance final food product quality and nutritional value, while improving food safety.  Novel edible films and coatings formulated with natural antibacterial essential oils and food packaging systems to improve food safety will be discussed.  Applications of nanoscience to edible films will also be discussed. Innovazioni nella lavorazione di nuovi prodotti alimentari per migliorare la sicurezza alimentare e la saluteRiassuntoLe nuove tecniche di lavorazione dei prodotti alimentari possono essere utilizzate per migliorare la sicurezza delle colture specializzate e dei loro co-prodotti, migliorando nel contempo la sostenibilità delle operazioni di trasformazione agro-alimentare e valorizzando la qualità nutrizionale complessiva dei cibi sia per i consumatori nazionali che internazionali. In questo lavoro si tratterà della potenzialità di queste nuove tecniche, molte delle quali sono state sviluppate presso l’USDA, il Dipartimento Americano per l’Agricoltura, nel centro di ricerca regionale occidentale di Albany, California ed in alcuni casi sono già state commercializzate attraverso partnership con l’industria. Le tecnologie innovative come l’utilizzo di film edibili, i trattamenti con ultravioletti, con infrarossi e con energia solare, possono migliorare la qualità e il valore nutrizionale del prodotto finale, migliorando nel contempo la sicurezza alimentare. Saranno poi trattati i nuovi film edibili e i rivestimenti formulati con oli essenziali antibatterici naturali e i sistemi di confezionamento degli alimenti per migliorarne la sicurezza alimentare. Si affronterà inoltre anche il tema dell’applicazione della nanoscienza ai film edibili.